Exploring The Non-ELT Students’ Gaming Experience in Acquiring the English Vocabulary - Dhafa Bima Wijaya Putra (Journal of Applied Linguistics and English Education, 2024)
Different digital technologies, especially video games, which are used to assist students in acquiring language, have been examined by researchers. However, studies exploring non-ELT students’ gaming experience in acquiring a second language (L2) vocabulary are sparsely investigated. Therefore, this study explores how non-ELT students’ gaming experience assists them in acquiring their second language (L2) vocabulary. The data of this study were gained from non-ELT students’ experiences. Four non-ELT students were interviewed, and the data from the interview were analyzed through thematic analysis. Several initial questions given to the non-ELT students were used to tell their game experience. The results of this study indicated that the games, notably Multiplayer Online Battle Arena (MOBA), First Person Shooter (FPS), Role Playing Games (RPG), have the potential to assist non-ELT students in acquiring second language (L2) vocabulary. Several principal reasons related to how the gaming experience helps the students in acquiring new vocabulary emerged in this study.